Insights into the Antecedents of Fast-Food Purchase Intention and the Relative Positioning of Quality. Issue 2 (3rd April 2018) - Harun, Ahasan; Prybutok, Gayle; Prybutok, Victor R.
ABSTRACT: This research develops and tests a theoretical framework that posits and examines factors affecting purchase intention in the fast-food industry. This study proposes a research model and investigates the complex interrelationships portrayed in the model after extracting relevant antecedents from the extant literature and contextualizing them to the fast-food restaurant industry. Anchored in the theoretical framework of social identity theory (Tajfel and Turner 1979 ), the theory of reasoned action (Fishbein and Ajzen 1975 ), and signaling theory (Spence 1973 ), this article evaluates the relationships among antecedents by using a survey to explore the consumer decision-making process and then by evaluating the proposed framework through partial least squares structural equation modeling (PLS-SEM). This study contributes to the extant literature by: a) identifying antecedent constructs of purchase intention within the fast-food industry; b) integrating these constructs into the first fast-food purchase intention model; c) providing practitioners an opportunity to tailor their marketing initiatives to specific consumer segments using importance-performance map analysis at both the construct and indicator levels; d) supporting a unique platform for benchmarking against existing brands in the same industry and brands from other industries. Findings also suggest that though quality is important, other antecedents account for more variation in why consumers intend to purchase fast food. Such a finding is actually positive if it implies a relatively high level of quality is homogeneous and expected within the industry, but the relative importance of quality has important implications for future research directions and provides insights for quality professionals.